Preparation of UV-curable gelatin derivatives for drug immobilization on polyurethane foam: Development of wound dressing foam - Woo, Hee-Dong; Park, Kyoung-Tae; Kim, Eun-Hye; Heo, Yun; Jeong, Jin-Hong; Pyun, Do-Gi; Choi, Chang-Soon; Lee, Jae-Gwan; Han, Dong-Keun; Nah, Jae-Woon; Son, Tae-Il (POLYMER SOC KOREA, 2015)
UV-curable azidophenyl-fish gelatin (azidophenyl-f.gel) for developing a wound-dressing foam was prepared by introducing the photo-reactive azidophenyl group of N-4-(azido)-benzoyloxysuccinimide (ABS) to fish gelatin. The structure of prepared azidophenyl-f.gel was identified by H-1 NMR and FTIR. The biocompatibility of azidophenyl-f.gel was demonstrated through a cell cytotoxicity experiment. In order to demonstrate that azidophenyl-f.gel is photo-cured on polyurethane foam by UV irradiation, a patterning test was conducted, and the protein immobilization of azidophenyl-f.gel was demonstrated through fluorescence microscopy by using FITC-BSA. The protein release pattern in relation to the concentration of azidophenyl-f.gel and the number of underlying layers of polyurethane foam was observed, and the effect of the protein release pattern on cell growth was observed through cell proliferation. Water absorbency and moisture vapour transmission rate (MVTR) tests were conducted to measure the performance of the wound dressing foam, and a wound healing effect was observed through an in vivo animal experiment. These results demonstrate that UV-curable azidophenyl-f.gel is biocompatible and can immobilize protein by UV irradiation. It is a useful material that can be applied to the underlying layer of wound dressing foam to induce rapid wound healing by gradually releasing immobilized protein.
Keywords: EPIDERMAL-GROWTH-FACTOR; FISH GELATIN; ARTIFICIAL SKIN; CROSS-LINKING; CHEMICAL IMMOBILIZATION; SUSTAINED-RELEASE; IN-VITRO; BIODEGRADATION; FILMS; BIOCOMPATIBILITY